Altered immunometabolic response to fasting in humans living with obesity - Helena Neudorf; Roderick E. Sandilands; Spencer Ursel; Hillary Shaba; Darren Barg; Takeshi Tsusaka; María Dolores Moya-Garzón; Erica Vaz; Patricia Schimweg; Emily L. Goldberg; Jonathan Z. Long; Karsten Krüger; et al. (iScience)
Summary: Fasting and ketosis are gaining interest for treating obesity-related immunometabolic dysfunction. We aimed to (1) characterize systemic and T cell immunometabolic responses to a 48-h fast in humans and (2) determine if responses differed between individuals with (O-BMI) and without (L-BMI) obesity (n = 16 per group). Despite similar increases in systemic fat oxidation, increases in blood β-hydroxybutyrate (BHB), BHB-amino acid conjugates, and lysine β-hydroxybutyrylation were blunted in obesity. T cells from the L-BMI group upregulated their relative capacity for fat oxidation while the O-BMI group did not. The O-BMI group had a greater proportion of Th17 cells and secreted more interleukin-17 (IL-17), even after fasting. CD8 expression decreased in both groups and CD4 expression only decreased in the L-BMI group. The balance of anti-to pro-inflammatory cytokines increased less in the O-BMI group. Collectively, these findings show that humans living with obesity have a blunted systemic and T cell immunometabolic response to fasting. NCT05886738.